Shri Dhirubhai Ambani with printing master Shanbaug - Reliance Industries Limited (2022)
Printing master Shanbaug, who joined Reliance in its early days and helped set up Reliance Textiles, looks on as Shri Dhirubhai Ambani explains to foreign exporters the mill’s 12-colour automatic roller printing plant, imported from Switzerland.